Stigma and discrimination toward people living with HIV/AIDS and factors affecting it in Sarawak, Malaysia: a community based cross sectional study - Lemin, A.S.; Rahman, M.R. (Malaysian Medical Association, 2017)
Introduction: Issue of stigma and discrimination not only related to people living with HIV/AIDS (PLWHA) but the community around them. The study aimed out to determine the level of stigma and discrimination toward PLWHA by community in Sarawak and determine the factors affecting it. Methods: A community based cross sectional study was conducted from June to November 2016, among 900 community in Sarawak via multistage sampling with gender stratification (450 male, 450 female). Data were collected using interviewed-guided questionnaires. Socio-demographic, knowledge on HIV/AIDS transmission, history HIV testing, perceived HIV disclosure, communication on HIV/AIDS and risk behaviour of HIV/AIDS. Hierarchical multiple regression models were fitted to identify associated factors for HIV/AIDS related stigma and discrimination toward PLWHA. Results: The mean age for male and female respondents was 41.57 (13.45) and 41.57 (13.45) respectively. The HIV/AIDS related stigma and discrimination was higher among female than male respondents. There was a significant negative correlation between knowledge on HIV/AIDS score and HIV/AIDS related stigma and discrimination score for both gender (p<0.01). However, religion, occupation, average household income and history of HIV testing were the strongest correlates of HIV/AIDS related stigma and discrimination among female, whereas ethnicity and communication were among male respondents in the multivariate analysis. Conclusion: HIV/AIDS related stigma and discrimination toward PLWHA coexisted among community in Sarawak, and this urged for specific intervention strategies by promoting de-stigmatisation of HIV/AIDS and tailored socioculturally.